Comparative Gene Finding Models, Algorithms and Implementation (Second Edition) - Axelson-Fisk, Marina (Springer, 2015)
The first edition of Comparative Gene Finding: Models, Algorithms and Imple mentation was published in March 2010. Since then a lot has happened and the field is gradually changing. A main driving force has been the ever-increasing use of next-generation sequencing (NGS) technology, which is revolutionizing a manifold of related fields. The pressure on computational methods and tools to handle these large amounts of data is greater than ever. In particular, since the “old” sequence analysis tools are not well adapted to the new situation with a huge data volume, much shorter read lengths, and an increased level of sequencing errors...